Applications and Analyzes of Artificial Intelligence in Enhancing English Vocabulary - Selvi, V. Thamil; K, Thirumoorthi (Recent Research Reviews Journal, 2024)
Vocabulary is a fundamental aspect of language proficiency and plays an essential role in the personal and professional lives of people. Vocabulary development is a challenging task in which the learners face various issue such as retaining, recalling, and using the new words after their initial exposure. Learning isolated words without their contextual meaning sometimes leads the learners to boredom. Moreover, difficulties in pronunciation and lack of appropriate usage in everyday contexts can further impede vocabulary development. Artificial Intelligence has the potential to revolutionize vocabulary learning by making it more personalized, engaging, and efficient. AI can improve vocabulary acquisition and retention through techniques like repetition at fixed time intervals, adaptive learning, NLP (natural language processing), contextual examples, and quick feedback AI addresses the diverse needs of learners and helps them acquire and retain vocabulary more effectively. This study tries to explore learning possibilities by incorporating AI technologies in English vocabulary development by comparing different platforms that facilitate enhanced learning outcomes, to address the unique needs of each learner, and provide a more dynamic and engaging learning environment in enthusiastic ways.